What are the Trends in Women’s Labour Force Participation in Turkey? - Karaalp-Orhan, Hacer Simay (European Journal of Sustainable Development, 2017)
Labour force participation (LFP) by women is an important driving force of the economic growth and sustainable development. However, one of the salient characteristics of Turkish labour market is the distinctly lower female labour force participation rate (FLFPR). In 1955, the FLFPR was 72%, which decreased to 32.5 % in 2016. Further, it is very low as per the EU–28 (52%) and OECD (51.9%) standards. The reasons of low FLFPR in Turkey are multidimensional. On the one hand, it could relate, to some extent, to the deep-rooted traditional gender roles (socio-cultural), and on the other hand, to the economic barriers. The process of urbanization and agricultural shedding are the two driving forces contributing to this decreasing trend. Thus, FLFPR in Turkey need to be improved through sustaining investment on education and creating job opportunities for the women. Government regulations should aim at promoting formal employment for undereducated women and increasing the quality of jobs. Many women could be encouraged to work by offering affordable childcare. Sustaining investment on the education of girls and women would also improve FLFPR and access to higher education would increase the LFP of women in Turkey. Keywords: female labour force participation rate, labour market, Turkey